Estimating risk on the capital market with VaR method - Sinisa Bogdan; Suzana Baresa; Zoran Ivanovic (UTMS Journal of Economics, 2015)
The two basic questions that every investor tries to answer before investment are questions about predicting return and risk. Risk and return are generally considered two positively correlated sizes, during the growth of risk it is expected increase of return to compensate the higher risk. The quantification of risk in the capital market represents the current topic since occurrence of securities. Together with estimated future returns it represents starting point of any investment. In this study it is described the history of the emergence of VaR methods, usefulness in assessing the risks of financial assets. Three main Value at Risk (VaR) methodologies are decribed and explained in detail: historical method, parametric method and Monte Carlo method. After the theoretical review of VaR methods it is estimated risk of liquid stocks and portfolio from the Croatian capital market with historical and parametric VaR method, after which the results were compared and explained.
Keywords: G17; 330; Value at Risk; Parametric; Monte Carlo; Capital Market